Heart rate variability during mindful breathing meditation - Natarajan, Aravind (Frontiers in Physiology, 2023)
We discuss Heart Rate Variability (HRV) measured during mindful breathing meditation. We provide a pedagogical computation of 2 commonly used HRV metrics, i.e. the root mean square of successive differences (RMSSD) and the standard deviation of RR intervals(SDRR), in terms of Fourier components. It is shown that the RMSSD preferentially weights higher frequency Fourier modes, making it unsuitable as a biosignal for mindful breathing meditation which encourages slow breathing. We propose a new metric called the autonomic balance index (ABI) which uses Respiratory Sinus Arrhythmia to quantify the fraction of HRV contributed by the parasympathetic nervous system. We apply this metric to HRV data collected during two different meditation techniques, and show that the ABI is significantly elevated during mindful breathing, making it a good signal for biofeedback during meditation sessions.